1994
DOI: 10.1016/s0741-5214(94)70034-6
|View full text |Cite
|
Sign up to set email alerts
|

Death and adverse cardiac events after carotid endarterectomy

Abstract: Independent clinical variables can help determine patients at increased risk for perioperative myocardial infarction or operative death. Patients in Goldman classes III and IV are at increased risk for adverse events. Carotid surgery can be performed safely in our medical community.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0
1

Year Published

1995
1995
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 18 publications
1
12
0
1
Order By: Relevance
“…82 A similar significant correlation of surgical cardiac morbidity and mortality was demonstrated in a retrospective study of 562 CEs, in which cardiac risk was stratified according to Goldman class I to IV and clinically silent CHD. 83 In the Veterans Affairs trial of CE for asymptomatic disease, a subgroup of patients without overt history of CHD but with other associated atherosclerotic vascular risk factors had a high perioperative risk of cardiac events similar to that of patients with symptomatic CHD. 75 No study with adequate statistical power has shown absence of association with CHD, including clinically silent disease, with morbidity after CE.…”
Section: In the Setting Of Cementioning
confidence: 99%
“…82 A similar significant correlation of surgical cardiac morbidity and mortality was demonstrated in a retrospective study of 562 CEs, in which cardiac risk was stratified according to Goldman class I to IV and clinically silent CHD. 83 In the Veterans Affairs trial of CE for asymptomatic disease, a subgroup of patients without overt history of CHD but with other associated atherosclerotic vascular risk factors had a high perioperative risk of cardiac events similar to that of patients with symptomatic CHD. 75 No study with adequate statistical power has shown absence of association with CHD, including clinically silent disease, with morbidity after CE.…”
Section: In the Setting Of Cementioning
confidence: 99%
“…Several groups have reported risk factors associated with stroke or death following CEA, with the intent of improving preoperative risk assessment and patient selection. 4–8 Across these studies, the most consistent risk factor found to predict stroke or death following CEA has been preoperative neurologic symptoms. Other variables associated with increased operative risk have included emergent operation, 4 renal failure, 8 and diabetes.…”
mentioning
confidence: 99%
“…It is also possible that the severity of coronary artery disease differed between the two studies. In retrospective study, Musser et al,4 showed that CAE patients in Goldman Cardiac Risk Classes I and II were at much lower risk (1.1%) for myocardial infarction that patients in Classes III and IV (12.5%, P = 0.0001). To assess this issue in future, consideration should be given to prospective classification of patients according to cardiac functional class and a cardiac risk index.3 Can we be reassured by the present results?…”
Section: Editorialmentioning
confidence: 97%
“…I1 est aussi possible que la gravit6 de la maladie coronaire ait diff~rt. Dans leur 6tude rttrospective, Musser et al 4 ont montr6 que les candidats /t rEAC classts Iet II sur l'tchelle de Goldman 6taient beaucoup moins/~ risque (1,1%) d'infarctus du myocarde que les patients de classes III et IV (12,5%, P = 0,0001). A ravenir, pour 6valuer cet aspect, il faudrait songer classer les patients prospectivement selon leur fonction cardiaque et leur assigner une cote de risque cardiaque.…”
Section: Editorialunclassified